Analysis on Utilization of Biology Laboratory and School Environment in Biology Learning for Tenth Grade Students of Senior High School in Jepara Regency (Universitas Negeri Semarang, 2018)
The application of 2013 curriculum had teacher to do scientific oriented learning. In fact, scientific oriented learning has not been applied fully in real life. Some obstacle factors are the lack of facility and teacher preparation. This research aims for: (1) analyzing facilities of biology laboratory and school environment, (2) analyzing the utilization of biology laboratory, (3) analyzing the utilization of school environment as learning source of biology subject for first semester of tenth grade students of senior high school. This is a descriptive qualitative research done in seven senior high schools in Jepara Regency. The subjects of this research are tenth grade biology teachers, tenth grade science major students, and vice headmaster (facility division). Data tabulation uses observation, interview, questionnaire, and documentation. Data triangulation uses source and method triangulation. Data analysis uses descriptive. Analysis result provides: 1) the laboratory facility in seven senior high schools in Jepara Regency can be included in “good: category even though it does not fill all the standardization of Permendiknas Number 24, 2007; facility of school environment is in below good category, 2) the utilization of laboratory in biology learning for tenth grade in first semester is in good enough category, 3) the utilization of school environment in biology learning for tenth grade in first semester is in good category. Some factors that influence categories are management of facility, lesson plan made by teachers, teacher understanding about biology material in scientific approach, teachers and students customary to scientific approach, and time allocation.